2018
DOI: 10.1128/jvi.02258-17
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies against Occludin Completely Prevented Hepatitis C Virus Infection in a Mouse Model

Abstract: Hepatitis C virus (HCV) entry into host cells is a multistep process requiring various host factors, including the tight junction protein occludin (OCLN), which has been shown to be essential for HCV infection in cell culture systems. However, it remains unclear whether OCLN is an effective and safe target for HCV therapy, owing to the lack of binders that can recognize the intact extracellular loop domains of OCLN and prevent HCV infection. In this study, we successfully generated four rat anti-OCLN monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 61 publications
4
35
0
Order By: Relevance
“…Using kinetic assays in polarised cells, this study also showed that OCLN plays a role subsequent to SR-BI, CD81 and CLDN1 131. These results were recently confirmed in kinetic assays using anti-OCLN monoclonal antibodies (mAbs) directed against either the ECL1 or ECL2 of OCLN 132. How and where HCV interacts with OCLN as well as what pool(s) of OCLN is(are) involved in this process remain to be further characterised.…”
Section: Tj Proteins and The Gi Tractmentioning
confidence: 52%
“…Using kinetic assays in polarised cells, this study also showed that OCLN plays a role subsequent to SR-BI, CD81 and CLDN1 131. These results were recently confirmed in kinetic assays using anti-OCLN monoclonal antibodies (mAbs) directed against either the ECL1 or ECL2 of OCLN 132. How and where HCV interacts with OCLN as well as what pool(s) of OCLN is(are) involved in this process remain to be further characterised.…”
Section: Tj Proteins and The Gi Tractmentioning
confidence: 52%
“…Shimizu et al [19] analyzed the relationship between the occludin molecule, a tight junction protein and the expression of which is dependent on Tacstd-2, and Hep C virus cell entry. Using a mouse model, it was shown that Hep C viral entry was prevented with anti-occludin antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al reported synergistic effects of anti-CLDN1 mAb with direct-acting antivirals as antiviral approaches for difficult-to-treat patients [126,127]. Confirming the functional role of OCLN in HCV entry, previous mechanistic monoclonal antibodies targeting ECL2 of OCLN were efficient in the prevention of infection both in cell culture and human liver chimeric mice without detectable side effects [114,128,129].…”
Section: Tight Junction Proteins and Hcv Infectionmentioning
confidence: 94%
“…OCLN on the other hand, is believed to act downstream of the other cell entry factors CD81, CLDN1, and SRB1 during the HCV entry process [113,114]. OCLN interacts with HCV surface glycoprotein E2 via its extracellular loop 2 (ECL2) [115].…”
Section: Tight Junction Proteins and Hcv Infectionmentioning
confidence: 99%